1982
DOI: 10.1029/jb087ib02p00936
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of seismic data from hydraulic fracturing experiments at the Fenton Hill, New Mexico, hot dry rock geothermal site

Abstract: An attempt was made to synthesize the results of active seismic experiments carried out by the Los Alamos National Laboratory's Hot Dry Rock Project staff for determining the geometrical and physical properties of the fracture system produced by hydraulic fracturing in a hot, low‐permeability rock. Interpretation of data from several reflection, transmission, and attenuation experiments using seismic probes in the frequency range from a few hundred to more than 104 Hz led us to postulate the existence of a hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Studies at deep-sea hydrothermal vents and geothermal sites on land have shown that seismic activity can affect hydrothermal flow by perturbing the thermal state and/or permeability structure of the local crust [Aki et al, 1982;Bame and Fehler, 1986;Ferrazzini et al, 1990;Bianco et al, 2004;Foulger et al, 2004;Wilcock, 2004;Cuenot et al, 2006]. While these observations provide intriguing evidence for seismic perturbation of hydrothermal flow, the extent to which they may be generalized is not clear.…”
Section: Introductionmentioning
confidence: 79%
See 1 more Smart Citation
“…Studies at deep-sea hydrothermal vents and geothermal sites on land have shown that seismic activity can affect hydrothermal flow by perturbing the thermal state and/or permeability structure of the local crust [Aki et al, 1982;Bame and Fehler, 1986;Ferrazzini et al, 1990;Bianco et al, 2004;Foulger et al, 2004;Wilcock, 2004;Cuenot et al, 2006]. While these observations provide intriguing evidence for seismic perturbation of hydrothermal flow, the extent to which they may be generalized is not clear.…”
Section: Introductionmentioning
confidence: 79%
“…Flow-induced microearthquakes generated by volume change mechanisms have been observed in geothermal areas [e.g., Ross et al, 1996;Miller et al, 1998;Foulger et al, 2004] and hydraulic fracturing experiments [e.g., Aki et al, 1982;Cuenot et al, 2006;Julian et al, 2007;Šílený et al, 2009], but this is the first time that a network small enough to detect and locate them has been deployed at a deep-sea hydrothermal field.…”
Section: Discussionmentioning
confidence: 99%
“…This effect has been known for more than 30 years, e.g. [4,5], and has been observed in areas, such as Indonesia, the Philippines, Japan, North and South America, and New Zealand. In most cases of induced seismicity, many events are generated each year, usually with magnitudes smaller than ML=3 and hence without economic consequences.…”
Section: Table Of Contents Introductionmentioning
confidence: 99%
“…The notion of "time lapse" seismology goes back at least 20 years when Aki proposed the method for analysis of hydrofracturing in petroleum and geothermal wells [Aki, et al, 1982]. The character of the seismic reflections in subduction zones can vary with time for at least three reasons: 1) when the state of stress on a horizon of interest varies with time a) as a result of an earthquake on the fault (over seconds), b) as a result of an earthquake in the region which changes the regional stress pattern (Coulomb stresses, over days, months and years), or c) as a result of slow deformation (over tens of years); 2) when the drilling process itself changes the in situ pressure conditions on the fault by relieving whatever pressure anomaly may have originally existed (over hours to years); and 3) when the seismic acquisition system changes.…”
Section: Monitoring Time-dependent Effectsmentioning
confidence: 99%